導言: Introduction - DU, Zhizheng (International Journal of Chinese & Comparative Philosophy of Medicine, 2000)
LANGUAGE NOTE | Document text in Chinese 儘管今天的醫學科學有了巨大的進步，儘管醫學仍在竭盡全力挽救一切生全命，但是，誰都知道，醫學仍不是萬能的，並不是任何治療都是有效和有益的。如何對待那些在今天看來仍是無益或無效的治療？本期“放棄治療”的主題，我們相信會引起廣大讀者的興趣的。 DOWNLOAD HISTORY | This article has been downloaded 11 times in Digital Commons before migrating into this platform.